2004
DOI: 10.1068/p5255
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Auditory and Visual Apparent Motion Presented Individually and with Crossmodal Moving Distractors

Abstract: Unimodal auditory and visual apparent motion (AM) and bimodal audiovisual AM were investigated to determine the effects of crossmodal integration on motion perception and direction-of-motion discrimination in each modality. To determine the optimal stimulus onset asynchrony (SOA) ranges for motion perception and direction discrimination, we initially measured unimodal visual and auditory AMs using one of four durations (50, 100, 200, or 400 ms) and ten SOAs (40-450 ms). In the bimodal conditions, auditory and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 28 publications
(51 reference statements)
2
22
2
Order By: Relevance
“…The direction of visual stimuli can capture the direction of auditory apparent motion but it has not yet been shown that the direction cues in the auditory stimuli can capture the direction of visual apparent motion Soto-Faraco et al, 2004b;Strybel and Vatakis, 2004). Likewise, the tactile motion distractors have a stronger influence upon the perception of auditory motion direction than auditory motion distractors do on tactile perception (Soto-Faraco et al, 2004a), and the visual motion distractors have a stronger influence on the perception of tactile motion direction than tactile motion distractors do on visual perception (Bensmaïa et al, 2006;Craig, 2006;Lyons et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The direction of visual stimuli can capture the direction of auditory apparent motion but it has not yet been shown that the direction cues in the auditory stimuli can capture the direction of visual apparent motion Soto-Faraco et al, 2004b;Strybel and Vatakis, 2004). Likewise, the tactile motion distractors have a stronger influence upon the perception of auditory motion direction than auditory motion distractors do on tactile perception (Soto-Faraco et al, 2004a), and the visual motion distractors have a stronger influence on the perception of tactile motion direction than tactile motion distractors do on visual perception (Bensmaïa et al, 2006;Craig, 2006;Lyons et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, auditory motion stimuli affect the direction of tactile motion (Soto-Faraco et al, 2004), mutual enhancement between vision and auditory motion has been observed (Strybel and Vatakis, 2004), and reaction times are fast to visuo-tactile motion then to either alone (Ushioda and Wada, 2007). Integration has also been shown for visuo-tactile apparent motion across fingers, but the integration seemed to occur at a high rather than low level (Harrar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they mention one important shortcoming of previous studies: the locations of the stimuli in both modalities were not spatially congruent, due to the use of headphones for the auditory stimuli. Strict spatial correspondence of visual and auditory stimuli, on the other hand, has been reported to be essential for the occurrence of multisensory integration effects (Meyer et al, 2005;Strybel and Vatakis, 2004), a fact that also found expression in the classical rules of multisensory integration as mentioned above.…”
Section: Introductionmentioning
confidence: 82%
“…The participants' task was to listen to each stimulus sequence and to perform a standard classification of the perceived quality of motion into one of four categories: (1) simultaneous presentation -all sounds were heard at the same time, (2) continuous motion -a single sound moved continuously from one side to the other, (3) broken motion -the movement was discontinuous, broken and interrupted and (4) succession of discrete events -the sounds were perceived successively, with no movement between them. This standard categorization system, originally developed by Briggs and Perrot (1972) for the study of AAM, has been used in a number of subsequent investigations on AAM (e.g., Perrot, 1974;Strybel et al, 1989Strybel et al, , 1990Strybel et al, , 1992 and in a modified form on VAM (e.g., Bruns and Getzmann, 2008;Getzmann, 2007;Strybel and Menges, 1998;Strybel and Vatakis, 2004). Prior to the experimental session, the participant was instructed about the experimental procedure, was thereafter given ten stimulus sequences as an example, and was afterwards allowed to ask questions to the experimenter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation